6G networks for artificial intelligence-enabled smart cities applications: A scoping review - Singh, Prabhat Ranjan; Singh, Vivek Kumar; Yadav, Rahul; Chaurasia, Sachchida Nand (Telematics and Informatics Reports, 2023)
Due to the increasing need for time with respect to industrial growth and the speeding up of human day-to-day work, network evolution is always the center of focus for research organizations. Artificial intelligence (AI), on the other hand, is playing an increasingly important role in automating systems, increasing efficiency, and ensuring high dependability in complicated activities. Network and AI research are generating a boom in IoT applications, as firms strive to serve their consumers with ever-improving features and functionality. In this article, we look at the evolution of network technology across time as well as the role of AI in the next generation of networks.  First, we will introduce the reader to the features of different network generations, technology used in. Second in the context of network evolution and AI, we will define the scope of IoT applications and their need in order to alleviate user demand. Consequently, we provide the requirements of advanced models in smart cities applications and insights on the development of future network for those applications. Our study showed that, though important features were introduced in the advanced automated networks, these are still to be tested under for automated applications that have strict requirements in terms of low latency, high reliability, and fast transmission.